2007
DOI: 10.1292/jvms.69.733
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence Analysis of VP2 Hypervariable Domain of Infectious Bursal Disease Virus Detected in Japan from 1993 to 2004

Abstract: ABSTRACT. Bursae of Fabricius were collected from 20 chickens diagnosed with infectious bursal disease virus (IBDV) infection from 15 prefectures in 1993 to 2004. Here we report the nucleotide sequence analysis of VP2 hypervariable domain of IBDV genome detected by reverse transcription-polymerase chain reaction from these samples. Ten sequences derived from 10 prefectures in 1996 to 2003 were of the classical type and other 10 sequences derived from 6 prefectures in 1993 to 2004 were of the highly virulent ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
(38 reference statements)
1
10
0
1
Order By: Relevance
“…This suggests that vaccine-like IBDV was prevalent even in IBD vaccine-free chicken farms in Japan. In addition, we previously detected a sequence in other layer chickens that were vaccinated with another live vaccine [21] that is identical to the sequence in broiler chickens in this study. The vaccinelike strains detected in this study may be widely distributed in Japan.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…This suggests that vaccine-like IBDV was prevalent even in IBD vaccine-free chicken farms in Japan. In addition, we previously detected a sequence in other layer chickens that were vaccinated with another live vaccine [21] that is identical to the sequence in broiler chickens in this study. The vaccinelike strains detected in this study may be widely distributed in Japan.…”
supporting
confidence: 55%
“…After introduction of such intermediate type vaccines, severe outbreaks of vvIBD have subsided. However, extensive usage of live vaccines in the field complicates the epidemiological situation of IBDV, because many vaccine-like viruses were detected in Japan as reported previously [21]. Recently, the numbers of IBDV vaccination-free poultry farms in Japan has increased due to the occurrence of fewer outbreaks and the increasing demand for drug-free food products.…”
mentioning
confidence: 92%
“…Genetic analysis has been the most widely used technique to characterize and classify IBDVs (Cao et al, 1998;Banda & Villegas, 2004;Hernández et al, 2006;Jackwood & Sommer-Wagner, 2007;Yamaguchi et al, 2007;Tomás et al, 2012). Studies have been mainly focused on the hypervariable domain of VP2 (hvVP2) because it codes for the most important immunogenic regions of the protein (Azad et al, 1987;Bayliss et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…These strain markers are determined by molecular typing techniques (e.g., restriction fragment length polymorphisms, real-time polymerase chain reaction, PCR) or sequencing. A more comprehensive classification is achieved by phylogenetic analysis using mainly the hvVP2 sequence; viruses are classified according with their association with reference strains in a well-supported clade that share a single common ancestor, i.e., evolutionary lineage (Jackwood & Sommer-Wagner, 2007;Yamaguchi et al, 2007;Kim et al, 2010;Islam et al, 2012). Phylogenetic trees using the hvVP2 region consistently recover the clades corresponding to the three IBDV strains (c, va and vv), and the clade composed of attenuated classic vaccine strains, usually denoted as "classic attenuated" (ca) IBDVs Wu et al, 2007;Xia et al, 2008;Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Two events were involved in this process: antigenic drift, which resulted in the rise of antigenic variants (avIBDV) in the United States [14,15], and the emergence of very virulent strains (vvIBDV) with the classical antigenic structure in Europe [16]. The new strains were later identified in different countries, particularly vvIBDV, which has become widespread throughout the world [17][18][19][20][21][22]. It has been suggested that the strong selection pressure generated by intensive vaccination of birds may lead to the emergence of viruses with new properties that are able to persist in immunized populations [10,23], and therefore, a virus obtained from an outbreak should be characterized based on its antigenic and virulent properties for more efficient control of the disease [10].…”
Section: Introductionmentioning
confidence: 99%